SINTESIS, PENGUJIAN, DAN KARAKTERISASI HIDROGEL BERBASIS SODIUM CARBOXYMETHYL CELLULOSE DAN CHITOSAN - Setyono Hari Adi; Nani Heryani (Widyariset, 2019)
Hydrogel, as a water super absorbent polymer, has a potential to improve irrigation efficiency in agricultural land. The objective of this research was to optimize hydrogel syntheses using environmentally friendly natural polymers, including sodium carboxymethyl cellulose (NaCMC), chitosan, and citric acid. Hydrogel was synthesized using the hydrothermal method at a temperature below 100 °C and using water as the primary medium. The results of this research showed that hydrogel which was synthesized with 2% w/v of NaCMC and 5% w/w of citric acid in 10% v/v of chitosan, which was cross-linked in 80 °C for 2 hours, was able to absorb water up to 350 times of its dry weights for 30 minutes. The maximum absorption rate of the produced hydrogel was up to 55 grams per minutes and was achieved during the first 3 minutes of free absorbency test.